Modeling Of Polymer Melt Flow In The Annular Channel Of A Disk Extruder - Novodvorskyi, V. V.; Ivanitsky, G. K. (Science and Transport Progress, 2023)
Purpose. Polymer products are used in industry due to their performance properties. The homogeneity of the melt is essential for the quality of the final product. Uniform distribution of components and properties ensures homogeneity of the product’s physical and mechanical characteristics. Insufficient homogeneity can lead to defects in the product. The homogenization zone plays an important role in ensuring a homogeneous melt. In a disc extruder, the homogenization zone consists of four consecutive channels. In order to describe the flow for the entire homogenization zone, it is necessary to model the first channel first. Therefore, the main purpose of this work is to model hydrodynamic and thermal processes during the flow of a non-Newtonian fluid in a straight annular channel in a non-isothermal regime, as well as to create a general procedure for further calculations for other channels. Methodology. The analysis of publications was carried out. The procedure for calculating the velocity and shear rate of the longitudinal and tangential melt flow, the effective melt viscosity, and the calculation of the melt temperature change along the length of the annular gap in an analytical form was developed. Findings. In accordance with the developed procedure, the values of tangential and longitudinal velocities and shear rates were calculated. The graphical dependences of the distribution of tangential and longitudinal velocities and shear velocities of the melt flow along the width of the annular channel, the distribution of pressure and the temperature of the polymer melt averaged over the width of the gap along the length of the annular channel are presented. Originality. In this work, a stationary flow in a straight annular channel was modeled for LDPE of the 15803-020 grade in a non-isothermal regime. A general procedure for further calculations for other channels of the homogenization zone has been developed. Practical value. The given calculation procedure can be applied to the following channels of the homogenization zone, which allows describing the melt flow for the entire homogenization zone.